On-farm reservoir to store groundwater A water efficient system for managing irrigation supplies in arid region of Gujarat - Kumar, Sanjay; Machiwal, Deepesh (Indian Farming, 2018)
The system of irrigation by using these emitters can be designed in integration with groundwater storage tanks located above the cultivated lands. The selection of different emitters should be based on the available pressure head, irrigation requirement of crops, soil type and quality of groundwater. The driptapes require minimum operating pressure and it also has minimum risk of chocking.Thus, the on-farm storage of groundwater benefits to farmers in arid area of Gujarat for managing their irrigation needs independent to time of electric supply for running the pumps. It saves the time of irrigation in interrupted power supply and overcomes the problem of low discharge from wells. The storage tanks can manage variable discharge from multiple wells for irrigation. It provides the desired rate of discharge and farmer can decide the same as per need of crop, property of soil and method of irrigation.